Analysis of Factors Associated with the Utilization of Healthcare Services for BPJS Participants in the Puskesmas Kampung Baru Working Area - Ulya Hasibuan, Fidella Naily; Arsania, Rara Fristi; Lubis, Syafirda Alifah; Gurning, Fitriani Pramita (Universitas Ibn Khaldun Bogor, 2024)
BPJS Kesehatan is a public law entity whose function is to organise a health insurance programme for all Indonesian, including foreigners, who work in Indonesia for at least six months. BPJS is divided into 2 groups, namely Contribution Assistance Recipients (PBI) and Non Contribution Assistance Recipients (Non PBI). The purpose of this study was to analyze the factors associated with the utilization of health services for BPJS health participants in the community in the working area of Puskesmas Kampung Baru, Medan Maimun Subdistrict, Medan City. This study used a cross sectional research design, as many as 100 samples using accidental sampling technique with the population of all BPJS participants in the working area of Puskesmas Kampung Baru. The results of the research with bivariate analysis showed that the p-value of age (0.647), gender (0.504), educational background (0.047), employment status (0.067), perception of officer attitude (0.008), length of waiting time (0.527), perception of BPJS (<0.0001), service accessibility (0.716). The statistical test results of this study indicate that there is a relationship between educational background, perceptions of officer attitudes, and perceptions of BPJS with the utilization of health services for BPJS participants. There is no relationship between age, gender, employment status, length of waiting time, service accessibility with the utilization of health services for BPJS participants.